2023
DOI: 10.33084/pengabdianmu.v8i1.4038
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Keuntungan Usaha melalui Pelatihan Pembudidayaan Varietas Cabai Unggul yang Tahan Organisme Pengganggu Tanaman dan Pengelolaan Pasca Panen

Abstract: Growing vegetables is a support to the family economy for farmers. The living conditions of fellow farmers are still far from good. The purpose of the Community Science and Technology Application in empowering Independent Advanced Farmer Groups is to provide solutions to problems in the aspects of production, management, marketing, management and post-harvest management. Thus, it has an impact in increasing the empowerment of partners. The methodology used in the application of community science and technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Incubation can develop MSMEs around customary forests, with a focus on skills development, mentoring, and access to markets. MSMEs incubation programs in social forests have the potential to improve community welfare and natural resource management [20]. The study showed that MSME incubation can provide significant social, economic, and environmental benefits.…”
Section: Msmesmentioning
confidence: 96%
“…Incubation can develop MSMEs around customary forests, with a focus on skills development, mentoring, and access to markets. MSMEs incubation programs in social forests have the potential to improve community welfare and natural resource management [20]. The study showed that MSME incubation can provide significant social, economic, and environmental benefits.…”
Section: Msmesmentioning
confidence: 96%